2011
DOI: 10.1504/ijtip.2011.043196
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative fuzzy-neural approach for forecasting the price of a DRAM product

Abstract: This paper presents a collaborative fuzzy-neural approach for accurately and precisely forecasting the price of a Dynamic Random Access Memory (DRAM) product, which is considered as one of the most important semiconductors widely used in various applications. In the collaborative fuzzy-neural approach, some experts from the application domain are invited to form a council. For some aspects, these experts put forward different points of view. These views are incorporated into the Back Propagation Network and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Tarui and Tarui [1] found that for DRAM long-term trends do exist and could be approximately modeled. The same phenomenon can also be observed in other industries [2][3][4][5][6][7][8][9][10]. Cupertino [11] was not so optimistic.…”
Section: Introductionsupporting
confidence: 58%
“…Tarui and Tarui [1] found that for DRAM long-term trends do exist and could be approximately modeled. The same phenomenon can also be observed in other industries [2][3][4][5][6][7][8][9][10]. Cupertino [11] was not so optimistic.…”
Section: Introductionsupporting
confidence: 58%